Ecosystem services from tropical forestry projects - The choice of international market actors - Sell, J.; Koellner, T.; Weber, O.; Pedroni, L.; Proctor, W.; Scholz, R. W. (Forest Policy and EconomicsForest Policy and Economics, 2007)
Ecosystem services from tropical forestry draw increasing attention from the public and private sectors. However, the decision making of market actors involved in transactions concerning ecosystem services is not well known and described. The goal of this paper is to describe preferences of market actors for tropical forestry projects that provide ecosystem services. Preferences were elicited within an explorative questionnaire survey directed to market actors from Europe, Japan, Latin America, South East Asia and the USA. Participants represent 71 companies and organisations including banks, certifiers, consultants, governmental organizations, industrial companies and associations, non-governmental organizations (NGOs), and re-insurance companies. Preferences were elicited based on a set of 12 criteria that were established in a previous survey with the same market actor groups. In one approach for preference elicitation, we applied discriminant analysis based on the assessments of criteria performances and attractiveness of two hypothetical forestry projects. According to their criteria performance, we labelled the projects bbusiness opportunityQ and bsustainabilityQ. The other approach was to let the participants weight the criteria directly without a given project context. The project bbusiness opportunityQ was significantly more attractive to participants than the project bsustainabilityQ. This contradicted strongly the results of the direct weighting procedure, where criteria associated with the project bsustainabilityQ received higher weights. We discuss this matter with regard to the phenomenon of framing effects. The discriminant model proved to be a useful method that allows the integration of a relatively large number of criteria that are necessary to cope with the complexity of decision problems related to tropical forestry. We critically compare our approach to choice experiments. In addition, we discuss implications of differences found between participants from tropical and non-tropical countries for the planning of market transactions for ecosystem services.